FAKTOR â FAKTOR YANG BERHUBUNGAN DENGAN PRESTASI BELAJAR PADA SISWA SEKOLAH DASAR NEGERI 47 KORONG GADANG KEC. KURANJI KOTA PADANG TAHUN 2014 - Oktavia, Nike Sari; Yulius, Okta Yuniatri (Jurnal Ipteks Terapan, 2014)
A major challenge in the development of nation is to biuld quality human resources are healthy, intelligent, and productive. Various factors that underlie the achievement of quality education. In a UASBN report on education, ranking Indonesia dropped from 58 to 62 among 130 countries in the world. The result of the bivariate analysis, there are 3 variable had a significant association with school performance that is nutritional status (p=0,000), duration of breastfeeding (p=0,038), maternal education level (p=0,001), as well as a variable that does not have a significant association wiyh school performance is economic status (p=0,699). It is hoped that the creation of coorperation between teachers and parents of students to pray attention to the factors that associated with increased student achievement so that students can get the maximum learning achievementDoi: 10.22216/jit.2014.v8i3.1